From accent to content: the effect of Spanish accents on message credibility - González-Martín, Ana María; Berd-Gómez, Rachid; Marín-Gutiérrez, Alejandro; Abrahamse, Elger (Frontiers in Communication, 2025)
The current study tested the potential effect of regional-accented speech on perceived credibility. Canarian and Madrid listeners were presented with a series of audio recordings in which speakers read out loud news items with either a Canarian or a Madrid accent, and they were tasked to rate the credibility of each news item. The within-subject manipulation of accent demonstrated a small but significant effect on credibility judgment, which was not moderated by listener’s origin. Specifically, in line with socio-linguistic stereotyping, news items presented in a Canarian accent were judged as less credible on average than news items presented in a Madrid accent. These findings are discussed both within the perspective of cognitive-linguistic theory, and within a sociological perspective.